ILLOCUTIONARY ACTS IN F.SCOTT FITZGERALD'S SHORT STORIES - Zulkiana, Kiki; Iskandar, Iskandar; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study analyzes the use of illocutionary speech acts in the two short stories by F.Scott Fitzgerald: such as The Bridal Party and Bernice Bob Her Hair. The objectives of this study are to 1) find out the types of illocutionary acts that are used in F. Scott Fitzgerald's short stories and 2) explore the analysis of the types of illocutionary acts by the characters in F. Scott Fitzgerald's short stories. The researcher used a descriptive qualitative research design in this study. The utterances in F.Scott Fitzgerald's two short tales serve as data sources. In this study, the researcher also employed Searle's (1979) speech act theory to solve the research problems. The results of this study reveal that the types of illocutionary acts utilized in the two short stories differ. The Bridal Party is the only short narrative that employs all sorts of illocutionary speech actions based on Searle theory. The researcher discovered all forms of illocutionary activities in this narrative (Representatives, Directives, Commissive, Expressive, Declaratives) which has a total of forty- three data. In addition, the researcher discovered just four forms of illocutionary activities in the second narrative, Bernice Bob Her Hair ( Representatives, Directives, Commissive, Declarative) with a total of thirty seven data.Keywords: Speech act, Illocutionary Act, Short Stories.